2010
DOI: 10.1186/ar2908
|View full text |Cite
|
Sign up to set email alerts
|

Chronic arthritis leads to disturbances in the bone collagen network

Abstract: IntroductionIn this study we used a mice model of chronic arthritis to evaluate if bone fragility induced by chronic inflammation is associated with an imbalance in bone turnover and also a disorganization of the bone type I collagen network.MethodsSerum, vertebrae and femur bones were collected from eight-month-old polyarthritis SKG mice and controls. Strength of the femoral bones was evaluated using three-point bending tests and density was assessed with a pycnometer. Bone turnover markers carboxy-terminal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…Osteopenia was generalized and not purely periarticular, as demonstrated by cortical thinning of femoral midshaft ( Figure 1C). Consistent with this significant bone loss, bone from SKG mice with chronic arthritis is reported to be mechanically fragile compared with that of age-matched BALB/c mice (17). Osteopenia in arthritic SKG mice is associated with increased osteoclast activity, as demonstrated by increased serum C-terminal telopeptide of collagen type I (CTX) after arthritis induction (Supplemental Figure 1D).…”
Section: Skg Arthritis Results In Osteopenia and Erosive Bone Lesionsmentioning
confidence: 68%
“…Osteopenia was generalized and not purely periarticular, as demonstrated by cortical thinning of femoral midshaft ( Figure 1C). Consistent with this significant bone loss, bone from SKG mice with chronic arthritis is reported to be mechanically fragile compared with that of age-matched BALB/c mice (17). Osteopenia in arthritic SKG mice is associated with increased osteoclast activity, as demonstrated by increased serum C-terminal telopeptide of collagen type I (CTX) after arthritis induction (Supplemental Figure 1D).…”
Section: Skg Arthritis Results In Osteopenia and Erosive Bone Lesionsmentioning
confidence: 68%
“…The relative distributions of mature and immature collagen were found to be equivalent in the arthritic and control groups of 5 months old SKG mice (Caetano-Lopes et al, 2009a). However, in the 8 months old SKG mice, we have observed that the ratio of the forward to backward signal was higher in arthritic animals than in control, which revealed a lower collagen density and organization (Caetano-Lopes et al, 2010). As an example, Figure 5 shows two multiphoton microscopy images from a) SKG mouse vertebrae and b) BALB/c mouse vertebrae.…”
Section: Scanning Electron Microscopy Semmentioning
confidence: 96%
“…BALB/c can be used as control for SKG mice. In five months (Caetano-Lopes et al, 2009a) and eight months (Caetano-Lopes et al, 2010) arthritic SKG mice, we have evaluated the bone structure by scanning electron microscopy and found that it was affected by the inflammatory disease. For example, the trabecular thickness was reduced from 70.91 ± 23.66 to 57.18 ± 16.78 μm in arthritic animals (CaetanoLopes et al, 2009a).…”
Section: Inflammatory Rheumatic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon could then predispose patients to bone fragility fractures [19]. Whether bone lesions predate and cause osteoarthritis or whether cartilage disease in osteoarthritis leads in turn to bone lesions is the subject of hot debate and extensive research.…”
Section: Bone Densitometrymentioning
confidence: 99%